A vinculação entre plano discursivo e metáfora situada no artigo de opinião - Lemos, Maria Clara Lucena de (2024)
In this paper, we investigate the relationship between the discursive plan category and the situated metaphor category in opinion articles. To this end, we consider the functional and cognitive dimensions underlying this relationship. Our general hypothesis is that there is a close relationship between the discursive plan of opinion articles and the emergence of situated metaphors in these texts. This relationship is expressed by the predilection of portions in figure position to elaborate the situated metaphor. In view of this relationship, we have developed an analysis that combines the functional and cognitive aspects to discuss the phenomenon focused on here. In terms of the functionalist approach, we draw on the assumptions of Functional Linguistics based on Givón (1995, 2001, 2011 [1979]), Traugott and Dasher (2002) and Furtado da Cunha, Costa and Cezario (2015), among others. With regard to Cognitivism, we draw on Tomasello (1998), Lakoff (1987), Fauconnier (1997), Lakoff and Johnson (2003 [1980]), among others. We also draw on Hopper and Thompson (1980), Haido (1996) and Lemos (2020) for discussions on discursive plan, and on Vereza (2007, 2013, 2016, 2017) for situated metaphor. Our investigative locus is the text and, because it extrapolates the traditional method of analysis of these theoretical strands, our work has a macrolinguistic approach. Methodologically, the research is qualitative with quantitative support and descriptive-explanatory. We used both inductive and deductive reasoning to observe the phenomenon analyzed and our corpus is composed of four opinion articles with different themes and authors. Our results show that there is a link between the analytical categories discursive plan and situated metaphor, so that the majority of situated metaphors (on-line) are used in a figure position, constituting a mechanism used in the service of argumentation in the analyzed texts. Furthermore, the findings show that the creation/understanding procedures of these metaphors produced on-line interact with processes of (inter)subjectivity and pragmatic inference, at the same time as they are supported by cognitive models. From a cognitive point of view, domain-general mechanisms, particularly image schemes and metaphorical and metonymic projections, support the mappings established ad hoc, enabling the interlocutor to undertake online interpretations, that is, changes in interpretation that do not affect the linguistic code definitively, but they are necessary to reach an understanding of the situated metaphor. In short, the form-function correlation can be explained in terms of the textual-discursive organization and the communicative and cognitive aspects examined in this thesis. From the point of view of textual-discursive organization, our research captures precisely the greatest recurrence of metaphors located in the textual portions that encode the figure. This finding corresponds, in functional terms, to the perceptual (cognitive) and communicative salience of these portions, in which the thesis and arguments of the text are found.